Development of intelligent road maintenance system mobile apps for a highway - Nurul Husna Mohd Jamail; Abdul Halim A. G.; Nor Shahida Mohd Jamail (Institute of Advanced Engineering and Science, 2020)
Roads are one of the main assets of a country where the network infrastructure offers economic and social benefits. It is understood that road maintenance would improve economic development and social benefits, and the poorly maintained road network would destruct mobility, raise accident rates, intensify isolation, poverty and vehicle operating costs. Unidentified road environment covers many aspects and based on that matter, it is important to improve the quality of inspection reports, whereby the efficiencies by mobile application shall be utilized. Developed system mobile apps have been found to be effective, versatile to use, as they can be used anywhere and at any time. The goal was therefore to recognize the types of defects, issues and deficiencies in current road maintenance practices and to develop a computerized highway maintenance program. The scope of the research will be limited to a case study at PLUS highway, connecting the north and south highway of peninsular Malaysia. The findings showed that road maintenance work is not adequately and effectively designed because it requires more time and includes a lot of paperwork. Due to this matter, the proposed mobile application would provide an invaluable added benefit to intelligent system of PLUS highway